2014
DOI: 10.1088/1674-1056/23/8/088102
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanoparticles: Preparation, properties, and applications

Abstract: Silicon nanoparticles have attracted great attention in the past decades because of their intriguing physical properties, active surface state, distinctive photoluminescence and biocompatibility. In this review, we present some of the recent progress in preparation methodologies and surface functionalization approaches of silicon nanoparticles. Further, their promising applications in the fields of energy and electronic engineering are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 127 publications
(213 reference statements)
0
26
0
Order By: Relevance
“…However, its inherent indirect band gap properties have limited its use in photovoltaic and light emitting diode applications. When the dimensions of Si nanoparticles (NPs) become comparable or smaller than Bohr radius of a bulk exciton ($4 nm for Si), [1][2][3][4] they undergo a remarkable transition from indirect to direct band gap semiconductor. 5 Under such conditions, band-to-band radiative recombination (rather than phonon-assisted indirect transitions) begins to dominate Si-NPs' luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its inherent indirect band gap properties have limited its use in photovoltaic and light emitting diode applications. When the dimensions of Si nanoparticles (NPs) become comparable or smaller than Bohr radius of a bulk exciton ($4 nm for Si), [1][2][3][4] they undergo a remarkable transition from indirect to direct band gap semiconductor. 5 Under such conditions, band-to-band radiative recombination (rather than phonon-assisted indirect transitions) begins to dominate Si-NPs' luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus each method requires optimization of chemical products, reducing agents or many steps for well controlled NP size. In recent years, pulsed laser ablation in liquid gathered immense interest as an efficient and alternative technique since it offers several advantages which can be listed as follows: (1) no material restriction compared to other techniques (2) no requirement for chemical precursors or reactions (3) no toxic by-products. However, the main drawback of this method is the limited control on the resulting size of the nanoparticles and their size distribution (homogeneity).…”
Section: Introductionmentioning
confidence: 99%
“…was found that an intracellular increase of Zn 2+ precedes cell death, indicating the intracellular dissolution of the ZnO NWs after uptake [112][113][114][115][116][117][118][119][120].…”
Section: Zinc Oxide Nanoparticles and Nanowiresmentioning
confidence: 99%
“…Currently, one of the more desirable Si NPs in the technology industry is ultra-fine silicon nanoparticles (with diameters of less than 10 nm). They are attractive in microelectronic devices, for the conversion of solar energy, in lightemitting diodes (LEDs), photopumped tunable lasers and in sensors [3][4][5][6][7][8][9]. Ultra-fine silicon nanoparticles are also promising candidates as anode active material for lithium-ion batteries [10,11].…”
Section: Introductionmentioning
confidence: 99%